1999
DOI: 10.1103/physrevlett.82.4420
|View full text |Cite
|
Sign up to set email alerts
|

Omnidirectional Superfluorescence

Abstract: A dense sample of atomic Rb vapor excited by a 4 ps laser pulse two-photon resonant with the 5S-5D transition in a large Fresnel number geometry emits a delayed coherent omnidirectional ir pulse on the 5D-6P transition. This superfluorescence emission involves a coherent population transfer to the 6P level and results in simultaneous directional uv emission and coherent population transfer back to the ground 5S state. This uv emission is a manifestation of parametric time-delayed four-wave mixing. For a compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 10 publications
5
26
0
Order By: Relevance
“…For a large outcoupled fraction, population n k−q and N q is built up in the final states and stimulates further scattering. This collisional amplification is not directional, and is similar to the recently observed optical omnidirectional superfluoresence [24].…”
Section: Suppression Of Impurity Collisionssupporting
confidence: 59%
“…For a large outcoupled fraction, population n k−q and N q is built up in the final states and stimulates further scattering. This collisional amplification is not directional, and is similar to the recently observed optical omnidirectional superfluoresence [24].…”
Section: Suppression Of Impurity Collisionssupporting
confidence: 59%
“…A crucial example of cascade cooperative emission, the so-called yoked SF, was first observed in cesium vapor by Brownell et al [17]. The experimental observation and theoretical description of the yoked SF with omnidirectional character (in rubidium vapor) were accomplished by Lvovsky et al [18,19]. Recently, Paradis et al obtained striking results while observing the yoked SF in laser-cooled rubidium atoms [20].…”
Section: Introductionmentioning
confidence: 77%
“…The same atomic configuration and associated radiation processes were recently considered by Lvovsky et al [18,19] and Paradis et al [20]. The delay between the input pulse and SF as a function of the number density of the atoms was presented by Lvovsky [19] by varying input pulse energy or the temperature of the vapor, and by Paradis [20] by loading different numbers of atoms into the magnetooptical trap.…”
Section: Introductionmentioning
confidence: 99%
“…Availability of a laserlike light source emitting radiation in a controlled directional fashion, from a point in the sky back toward a detector, should revolutionize remote sensing (8,9). Dogariu et al demonstrated the possibility of remote lasing of atmospheric oxygen by using sub-mJ picosecond UV laser pulses at 226 nm that produce a bright near-infrared (NIR) laser source at 845 nm wavelength using atomic oxygen as the gain medium (10).It has been proposed that a mirrorless laser can be used as a superradiant source where coherence is large, such as a coherence brightened laser (11)(12)(13)(14). This type of superradiance was first demonstrated in optically pumped HF gas (15).…”
mentioning
confidence: 99%
“…It has been proposed that a mirrorless laser can be used as a superradiant source where coherence is large, such as a coherence brightened laser (11)(12)(13)(14). This type of superradiance was first demonstrated in optically pumped HF gas (15).…”
mentioning
confidence: 99%